Financial Distress pada Usaha Kecil dan Menengah di Indonesia - Adinda, Yuniar; F. T, Kristanti (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
Financial distress became a dependent variable used in this study, with the aim ofknowing how the influence on current ratio, work capital to total assets (WCTA),company size, sales growth, managerial ownership, and institutional in small andmedium enterprises listed on IDX (Indonesia Stock Exchange). The populationselected for this study was 39 small and medium-sized companies in 2015-2019, witha sample of 9 companies selected. The data analysis model applied in this study islogistic regression analysis. The results of this study showed that current ratio, firmsize, sales growth, managerial ownership, and institutional ownership have nosignificant influence on financial distress. As for the ratio of work capital to totalassets has a significant influence on financial distress